2010
DOI: 10.1007/s00198-010-1332-0
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and bone health in community-dwelling older men: the CHAMP Study

Abstract: Although crude occupation-based SES scores were not significantly associated with bone health in older Australian men, specific sub-characteristics of SES, namely, marital status, living circumstances, and acculturation, were predictors of bone health in both Australia-born men and European immigrants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…This result is consistent with previous studies of postmenopausal women [6,22,23]. Most studies that have examined the relationship between SEP and bone health have used data from postmenopausal women, and only a few studies have examined the relationship in men [3,24,25]. In fact, those that have examined men have shown results inconsistent with our study: Elliot et al [25] showed an inverse relationship between SEP and BMD in a Caucasian male population, where men with higher SEP had lower BMD.…”
Section: Discussionsupporting
confidence: 83%
“…This result is consistent with previous studies of postmenopausal women [6,22,23]. Most studies that have examined the relationship between SEP and bone health have used data from postmenopausal women, and only a few studies have examined the relationship in men [3,24,25]. In fact, those that have examined men have shown results inconsistent with our study: Elliot et al [25] showed an inverse relationship between SEP and BMD in a Caucasian male population, where men with higher SEP had lower BMD.…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were observed in a study of middle-aged Norwegian women [8]. Nabipour et al showed that Australian elderly men who are married had a higher bone mineral content than those who lived alone [9]. Further, a recent study on Chinese elderly individuals assessed the relationship between osteoporosis and the amount of received social support [10].…”
Section: Introductionsupporting
confidence: 68%
“…Because marital status was associated with bone density and fracture in previous studies [69], we also controlled for marital status. This variable was categorized into two groups: (1) those who were currently not married (widowed, divorced or never married) and (2) those who were currently married.…”
Section: Methodsmentioning
confidence: 99%
“…The major predictor of greater hip fracture risk is low bone mineral density (BMD) in the femoral neck; yet, studies have not found strong associations between low SES and low femoral neck BMD [9,10,11,12,13]. Of the various indicators of adult SES, education level more than income, occupation, or wealth, has shown consistent associations with BMD [14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%